PERBEDAAN KADAR HEMOGLOBIN PADA IBU MENYUSUI DI DAERAH PEGUNUNGAN (SUMOWONO) DAN PESISIR PANTAI (BANDARHARJO) SEMARANG - Dewi Sulistyoningrum; Suhartono - -; M. Sakundarno Adi (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Background: Breastfeeding mothers are prone to anemia due to a decrease in maternal iron during breastfeeding and blood loss during labor. Hemoglobin is a protein that contains iron in red blood and functions to carry oxygen from the lungs to all body tissues. The plateau has an influence on hemoglobin levels which can cause hypoxia due to reduced oxygen partial pressure. The purpose of this study was to determine the differences of hemoglobin levels in breastfeeding mothers in mountainous areas (Sumowono) and coastal areas (Bandarharjo). Samples was found 33 breastfeeding mothers in mountains areas and 22 breastfeeding mothers in the coastal. Method of this research used design analytic observational was cross sectional design, selection of sample with purposive sampling. This study uses statistical analysis of Mann Whitney with ?=0.05. The result of this study get p value 0.278 where p > ? = 0.05, then Ho was accepted and can concluded that there were no differences hemoglobin levels of breastfeeding mothers in mountains and coastal areas. The conclusion of this study is average level of hemoglobin levels in breastfeeding mothers in mountains areas and coastel are no different.Keywords: Hemoglobin, Anemia, Breastfeeding Mothers, Mountains Areas, Coastal